Waste to Wealth: Art Production Formula in a Lockdown Situation - Ukim, Ime (Talenta Publisher, 2022)
In life, there are negative occurrences capable of throwing humanity into lockdown conditions, like the recent global pandemic - Covid-19, which caused lockdowns to be declared at different places across the globe. This made for the restriction of movement, resulting in the unavailability of raw materials, which in turn halted the production of goods which are not food or medicine. Art was not left out, as its production was equally held in abeyance. This paper projects a formula for continuity in art production in such a situation. Its objectives are to expatiate the basic requirements for art production and propose a viable formula for it in a lockdown situation. The paper employed the internet, analog, and digital libraries to review related literature and works and a descriptive research approach. Findings reveal that the basic requirements for art production are artistic skill, artistic idea; art material(s); and tools/equipment where necessary. Also, the artist’s main problem of unavailability of conventional materials during lockdown can be overcome by employing waste, freely available everywhere, for art production. The paper concludes that employing waste as material for art creation can keep the artist afloat in art production during the lockdown. It is recommended that artists not only employ waste for art creation in a lockdown condition but always for innovation and creativity in art praxis.